What to do about MatIntroKem? - Hansen, Thorsten (Improving University Science Teaching and Learning, 2023)
The introductory mathematics course offered to freshman students in chemistry and biochemistry has posed an insurmountable obstacle for too many students for more than a decade. The percentage of students failing the course has been on the order of 30% for more than ten years. This, of course, is a problem for each individual student, who wastes time that was better spent learning chemistry, and also for department finances. The number of students failing will never become zero, but ideally it could be cut in half. The objectives of this paper are to provide an analysis of the course, and to suggest some ideas for change or improvements. It will serve as a white paper for my work with Professor Tinne Kjeldsen to develop the course.